The Debate on the Notion of Corporeal Substance in Leibniz - Adomaitis, Laurynas; Jokubaitis, Alvydas (Problemos, 2014)
Leibnizian metaphysics is traditionally held to be idealistic. It means that reality is composed of soul-like substances whereas material bodies are mere phenomena. The traditional interpretation presupposes that Leibniz’s view has not changed during the mature period (from 1683 onward). Some commentators have recently challenged this view. They claim that either Leibniz (despite inconsistency) was both a realist and an idealist (Hartz), or changed his view on the nature of substance (Garber). The aim is to defend the traditional interpretation and to reply to the arguments by realist commentators.
Keywords: Leibniz; corporeal substance; idealism; realism